2014
DOI: 10.1038/jid.2013.323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Histamine-Mediated Attenuation of Acetylcholine-Induced Sweating via GSK3β Activation

Abstract: Sweating has been associated with the exacerbation of atopic dermatitis (AD) in diverse ways. Acetylcholine (ACh)-mediated sweating is known to be attenuated in AD, but its cause remains obscure. To address this issue, the impact of histamine on ACh-induced sweating was evaluated. Sweating was measured by counting the number of active sweat pores by the starch-iodine reaction and dynamic optical coherence tomography; sweat was visualized using two-photon excitation fluorescence microscopy in mice and the quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 48 publications
(48 reference statements)
1
47
0
Order By: Relevance
“…This effect of histamine was inhibited by a type 1-histamine receptor antagonist (5). Thus, the favourable effect of AH on the cases of patients with IPSF presented here might provide further evidence for our previous report (5). As previously mentioned, the treatment options for IPSF are limited and systemic steroid therapy has been applied to cases without spontaneous remission.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This effect of histamine was inhibited by a type 1-histamine receptor antagonist (5). Thus, the favourable effect of AH on the cases of patients with IPSF presented here might provide further evidence for our previous report (5). As previously mentioned, the treatment options for IPSF are limited and systemic steroid therapy has been applied to cases without spontaneous remission.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, we found that the inhibitory effect of histamine on acetylcholine-induced sweating occurred via phosphorylation of glycogen synthesis kinase 3β in sweat gland acinar cells (5). This effect of histamine was inhibited by a type 1-histamine receptor antagonist (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine is a factor common to both pathological conditions. It plays a major role in the pathogenesis of urticaria and also inhibits acetylcholine‐induced sweating . Through histamine H1 receptors, histamine inhibits secretion of sweat from secretory cells of sweat glands to suppress sudomotor activity .…”
Section: Treatment and Clinical Questionsmentioning
confidence: 99%
“…Beyond unambiguously showing aggravation of histamine-induced neurogenic flare starting at 2 min post-histamine pricks and lasting throughout the assessment period, this study also showed a significantly increased sudomotor activity on the fingertips during the conditioning pain stimulation indicative of increased sympathetic efferent fiber activity. The decrease in skin conductance within the prick area suggests a local histamine-induced desiccation of the skin immediately around the prick site (which was offset by a slight increase evoked by pressure conditioning stimulation), in line with the known hypohydrotic effect of histamine (Matsui et al 2014a(Matsui et al , 2014bMurota et al 2015).…”
Section: The Neurogenic Inflammatory Response Is Increased By Heterotmentioning
confidence: 58%